Rare Case Of Deep Neck Infection - Marolov, M; Milceska, E; Sulejmani, S; Arnautovska, B (My University, 2020)
Introduction: Deep neck infections are a serious but treatable group of infections affecting the deep cervical space and characterized by rapid progression and life-threatening complications. These infections remain an important health problem with significant morbidity and potential mortality. These infections most frequently arise from the local extension of infec - tions from tonsils, parotid glands, cervical lymph nodes, and odontogenic structures. They classically present with symptoms related to local pressure effects on the respiratory, nervous, or gastrointestinal tract (particularly neck mass/swelling/ induration, dysphagia, dysphonia, and trismus). The specific presenting symptoms will depend on the deep neck space involved (parapharyngeal, retropharyngeal, prevertebral, submental, masticator, etc) Objectives: To present a successful management of a 68 year old patient with severe deep neck infection, despite the unknown origin of the infection focus. Material and Methods: A 68 year old male patient visited ENT Clinic on day 1 without specific pain, only with slight neck edema in front of the laryngeal box. The edema was non painful and soft, without affection of lateral neck lymph nodes. Oropharyngoscopy - there were no pathologic findings. Fibernasolaryngoscopy - sufficient breathing canal, without specific pathological signs. The patient had diabetes mellitus, treated with oral antidiabetic drug for more than 5 years. The patient was set on double course –antibiotic per -os therapy (3rd gen. cephalosporin and macrolide), corticosteroids and painkiller. On day 3 the patient condition was getting worse so on his second visit to the ENT specialist his neck was swelled, red, warm and painful with severe edema spreading towards jugulum, and immediate hospitalization was required. The patient was set on double Antibiotic I.V therapy, I.V corticosteroids, and insulin injections. His biochemistry results showed severe raise of inflammatory parameters. Second day after the hospitalization his breathing was affected, led by fibernasolaryngoscopy evaluation that showed hyperemia of hypopharyngeal and laryngeal structures affecting the breathing space. Urgent tracheostomy and neck incision were performed under endotracheal anesthesia. During the neck incision massive purulent secretion was drained. The patient was left with an open wound for daily treat - ment and inspection. In the next days the patient’s neck incision was locally treated with antibiotic, and drained from pus. CT scan and microbiological swab and aspiration were performed during the next 5 days. The patient was switched to vancomycin after the microbiology results (Enterococcus). Results: After 15 days of constant care, twice daily local treatment of the wound, the inflammatory parameters started set - tling to normal values, and the local finding was improved. The larynx and hypopharynx inflammation was resolved. The patient was stable and subjective feeling was well. The main problem left was the intermediate skin defect due to prolonged treatment and skin necrosis. Conclusion: Deep neck infection can be capricious condition in which the time and reaction in treatment can be of life essence. Many other conditions and comorbidity can affect the course and the outcome of the treatment. Hospital treatment and constant follow up of the patient can give the healthcare professionals position to react accordingly.
Keywords: Neck infection; skin necrosis; diabetes mellitus